Brown oxidation additive and IC carrier plate browning method using same
Patent Information
- Application Number
- CN202510174051.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-18
AI Technical Summary
The existing browning technology is difficult to meet the high standards for IC carrier plate production, resulting in a decrease in production yield.
A browning additive for the IC carrier plate browning production process is provided, which contains active ingredients such as corrosion agents, crosslinking agents, plasticizers, and oxidizing agents. Through these components, a layer of organic metal film is formed on the copper surface to improve the uniformity and bonding force of the copper surface after browning.
It achieves low roughness, high peel strength, low insertion loss and good heat resistance to meet the production needs of IC carrier plate browning process.
Smart Images

Figure CN119640248A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of IC carrier board production and manufacturing, and in particular to a browning additive and an IC carrier board browning method using the same. Background Art
[0002] In recent years, as the integrated circuit industry has been moving towards small size and high integration, IC packaging has also been moving towards ultra-multiple pins, ultra-miniaturization and narrow pitch. IC substrates are developed based on HDI boards. They have the characteristics of high density, high performance and thinness. They are an upgrade of the traditional integrated circuit packaging lead frame. They are used in various chip packaging links and can play a key role in supporting, connecting, dissipating heat and protecting the chip.
[0003] The browning process is to form an organic metal conversion film on the copper surface through the micro-etching effect of the browning liquid on the inner copper film, which strengthens the bonding with the substrate and improves the thermal shock resistance and delamination resistance of the laminate. The browning liquid mostly uses an acidic system of sulfuric acid and hydrogen peroxide, and then adds specific organic matter. During the browning process, uneven and active micro-roughness is formed on the copper surface, which increases the contact area with the resin during lamination. The role of browning mainly includes removing grease and debris on the surface to ensure the cleanliness of the board surface; after browning, a uniform layer of fluff will form on the copper surface of the substrate, which will increase the bonding strength between the substrate and the resin, help avoid delamination, bursting and other problems, thereby improving the reliability and stability of the circuit board; by removing the oxides on the metal materials of the circuit board, the adhesion of the surface metal materials is increased, thereby improving the yield of the next process; for deformation welding of lead-containing solder, an oxide film will form on the surface of the circuit board, which can increase the solderability of the circuit board surface and facilitate welding; browning of the circuit board will form an oxide film, because copper oxide contains a certain amount of CuO and Cu2O, these oxides have certain conductive properties, which can help improve the conductivity of the circuit board.
[0004] At present, there are also some technical solutions related to browning, such as patent CN111826645A discloses a browning liquid for the inner copper foil of a circuit board, the ingredients of which include aqueous sulfuric acid solution, zinc sulfate, hydrogen peroxide, 2-mercaptobenzothiazole, 4-carboxybenzotriazole, sodium chromate, dodecylbenzenesulfonic acid, and polyvinyl alcohol, which can solve the defects of poor anti-peeling strength of the board after browning, weak tolerance to high-temperature thermal shock, uneven micro-etching, and poor interlayer bonding. Patent CN110527996A provides a browning liquid and its preparation method and application, wherein the browning liquid contains anhydrous copper sulfate, sulfuric acid, chloride, benzotriazole, citric acid and its derivatives, nitric acid, and hydrogen peroxide. The browning liquid has a high copper loading, a small amount of precipitation in the solution, a long service life, and low pollution. At the same time, it can effectively solve the problems of poor browning of different copper crystals and copper exposure in the browning of the patching alloy.
[0005] After continuous research and improvement, the existing browning technology has also overcome the blackening problem in the original process. The board shows the advantages of strong acid resistance, no pink ring, high peel strength, low operating temperature, safety and high efficiency. Browning technology has obvious advantages in production and manufacturing, and will become the mainstream in the surface treatment process of the inner layer of printed circuit boards. With the rapid development of the PCB industry and the continuous increase in market demand, the IC packaging substrate market has grown rapidly, and the technical difficulty of IC substrates is higher than that of PCBs. Compared with ordinary PCBs, IC substrates have the advantages of thinner boards, easier deformation, smaller through-hole diameters and line widths / line spacing. At the same time, their technical and production requirements are more stringent, which puts higher requirements on the density and refinement of PCBs. Although the existing browning technology has made good development progress, it is difficult for the existing technology to meet the standards for IC substrate production, resulting in a decrease in production yield. Therefore, there is an urgent need for a browning solution for IC substrates to meet the production requirements of modern IC substrates and high-frequency signal transmission. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a browning additive for an IC carrier board browning production process, comprising effective ingredients such as an etchant, a cross-linking agent, a plasticizer, an oxidant, etc., wherein the effective components can form a layer of organic metal film on the uneven active microscopic rough copper surface, effectively improving the uniformity and bonding strength of the copper surface after browning, so that the copper surface has low roughness, high peel strength, low insertion loss and good heat resistance, thereby meeting the production requirements of the IC carrier board browning process.
[0007] The objectives of the present invention are achieved through the following technical solutions.
[0008] Provided is a browning additive, which is composed of the following components per 100 parts by weight: 1.0-3.0 parts of a first corrosion inhibitor, 1.0-3.0 parts of a second corrosion inhibitor, 0.5-2.0 parts of a cross-linking agent, 0.5-2.0 parts of a plasticizer, 0.2-1.0 parts of an oxidant, and the balance is water; The structural formula of the first corrosion inhibitor is as follows: ; wherein R is F, Cl, Br or I; The second corrosion inhibitor is selected from at least one of guar gum (CAS No.: 9000-30-0), locust bean gum (CAS No.: 9000-40-2), and alginate (CAS No. 83-85-2); The mass ratio of the first corrosion inhibitor to the second corrosion inhibitor is 1:(0.5-2.0).
[0009] Preferably, the cross-linking agent is selected from at least one of bis(bipyridine)-4'-methyl-4-carbonylpyridinium ruthenium-N-succinimide ester bis hexafluorophosphate (CAS No.: 136724-73-7), 4-(azidosulfonyl)benzoic acid N-succinimide ester (CAS No.: 1427502-22-4), and 3-maleimidopropionic acid N-hydroxysuccinimide ester (CAS No.: 55750-62-4).
[0010] Preferably, the plasticizer is selected from at least one of oxazole-2-carboxamide (CAS No.: 884539-45-1), oxazole-4-carboxamide (CAS No.: 23012-13-7), and oxazole-5-carboxamide (CAS No.: 158178-93-9).
[0011] Preferably, the oxidant is selected from at least one of N-allylbenzylamine (CAS No.: 4383-22-6), 4-vinylbenzylamine (CAS No.: 50325-49-0), and N-benzylbutylamine (CAS No.: 780-25-6).
[0012] Preferably, the first corrosion inhibitor is prepared by mixing 1,2-diphenylethanedione, p-aminoanisole, p-halobenzaldehyde and acetic acid in water, reacting at 60-70° C. for 4-6 hours, and after the reaction, adjusting the pH of the resulting solution to 7-8, and then extracting with ethyl acetate to obtain the first corrosion inhibitor.
[0013] Preferably, the mass ratio of 1,2-diphenylethanedione, p-aminoanisole, p-halobenzaldehyde and acetic acid is (2-3):(2-3):(2-3):1, and more preferably, the mass ratio is 2:2:2:1.
[0014] The preparation method of the above-mentioned browning additive is as follows: weigh the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the remaining water in sequence and add them into a reactor, stir and mix them evenly at room temperature to obtain the browning additive, and seal and store it for later use.
[0015] The present invention also provides a method for browning an IC substrate, which comprises the following steps in sequence: Activation: Activating the IC substrate with an activation solution; the activation solution is an aqueous solution of the above-mentioned browning additive with a mass concentration of 3-4%; Browning: The IC substrate is browned using a browning solution; the browning solution is composed of the following components in mass fractions: 3-5% of the above-mentioned browning additive, 4-6% of sulfuric acid, 2-3% of hydrogen peroxide, and the balance is water.
[0016] Preferably, the activation treatment of the IC substrate with the activation solution is specifically performed by spraying the IC substrate with the activation solution at a spray pressure of 1.5±0.5 kg / cm 2 , time 35-50S.
[0017] Preferably, the browning treatment of the IC substrate with the browning solution is specifically performed by spraying the IC substrate with the browning solution at a spraying pressure of 1.5±0.5 kg / cm 2 , time 35-50S.
[0018] Furthermore, the above-mentioned method for browning the IC substrate further includes pickling, degreasing and water washing before the activation step.
[0019] In the browning additive of the present invention, the corrosion inhibitor includes a first corrosion inhibitor and a second corrosion inhibitor. The synergistic effect between the components is utilized to increase the adsorption coverage and adsorption stability, change the adsorption speed, thereby effectively improving the corrosion inhibition efficiency and achieving a better browning effect. Secondly, the corrosion inhibitor participates in the formation of the organic metal film, that is, a uniform and dense organic metal oxide layer is generated on the copper surface; the cross-linking agent in the present invention has the function of promoting cross-linking and coupling, has a strong adsorption force with the copper surface, is conducive to the formation of a multi-layer composite film on the surface of the copper foil, thereby significantly improving the quality of the organic metal film; the plasticizer in the present invention has a strong chemical activity, on the one hand, it is easy to form a coordination bond with metal copper and strongly adsorb on the surface of the copper foil, on the other hand, it has a strong polymerization effect with the semi-cured resin, and at the same time, the non-polar group part can form a hydrophobic protective film on the metal surface to inhibit the erosion of the corrosive medium; the oxidant in the present invention can form a moderately deep and uniform rough surface on the surface of the copper foil in an acidic medium, which provides favorable conditions for the formation of the organic metal film on the copper surface and the copper foil surface, and is conducive to increasing the contact area between the copper foil surface and the resin during pressing.
[0020] Therefore, the browning additive of the present invention can form an organic metal film on the uneven active microscopic rough copper surface, effectively improving the uniformity and bonding strength of the copper surface after browning, so that it has low roughness, high peel strength, low insertion loss and good heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.
[0022] Figure 1 is the reaction formula of the first corrosion inhibitor of the present invention; Figure 2This is a SEM image of the IC substrate after the browning process in Example 1 of the present invention; Figure 3 This is a SEM image of the IC substrate after the browning process in comparative example 13 of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The first corrosion inhibitor of the present invention is prepared by mixing 1,2-diphenylethanedione, p-aminoanisole, p-halobenzaldehyde and acetic acid in water, reacting at 60-70°C for 4-6 hours, adjusting the pH of the resulting solution to 7-8 with a sodium bicarbonate solution after the reaction, and then extracting with ethyl acetate to obtain the first corrosion inhibitor; the mass ratio of the 1,2-diphenylethanedione, p-aminoanisole, p-halobenzaldehyde and acetic acid is (2-3): (2-3): (2-3): 1, and more preferably, the mass ratio is 2:2:2:1. In order to further verify the effects of the first corrosion inhibitor and the browning additive of the present invention, the preparation method of the first corrosion inhibitor used in the following examples or comparative examples is as follows: According to the mass fraction of the raw materials, 5% of 1,2-diphenylethanedione (CAS No.: 134-81-6), 5% of p-aminoanisole (CAS No.: 104-94-9), 5% of p-halobenzaldehyde (wherein the halogen can be F, Cl, Br, I; p-fluorobenzaldehyde, CAS No.: 459-57-4; p-chlorobenzaldehyde, CAS No.: 104-88-1; p-bromobenzaldehyde, CAS No.: 1122-91-4; p-iodobenzaldehyde, CAS No.: 15164-44-0), 2.5% of acetic acid (CAS No.: 64-19-7), and the balance of water were added to a three-necked flask, and heated at 65°C for 5 hours. After the reaction was completed, the pH of the reactant was adjusted to 7 with sodium bicarbonate solution (CAS No.: 144-55-8), and then extracted with ethyl acetate (CAS No.: 141-78-6) to obtain the first corrosion inhibitor, whose structural formula is: .
[0025] The reaction formula of the first corrosion inhibitor is as follows Figure 1 shown.
[0026] Example 1 According to 100 parts by weight of the following formula, the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the balance water are weighed in sequence and added into the reactor, and stirred and mixed at room temperature for 30 minutes to obtain the browning additive of this embodiment, which is then sealed and stored for later use.
[0027] 1.5 parts of the first corrosion inhibitor, whose structural formula is: ; 1.5 parts of the second corrosion inhibitor, specifically guar gum; 1.0 part of a cross-linking agent, specifically bis(bipyridine)-4'-methyl-4-carbonylpyridinium ruthenium-N-succinimidyl ester bis-hexafluorophosphate; 1.0 part of plasticizer, specifically oxazole-2-carboxamide; 0.5 parts of an oxidizing agent, specifically N-allylbenzylamine; Distilled water balance.
[0028] Example 2 According to 100 parts by weight of the following formula, the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the balance water are weighed in sequence and added into the reactor, and stirred and mixed at room temperature for 30 minutes to obtain the browning additive of this embodiment, which is then sealed and stored for later use.
[0029] 1.5 parts of the first corrosion inhibitor, whose structural formula is: ; 1.5 parts of the second corrosion inhibitor, specifically locust bean gum; 1.0 part of a cross-linking agent, specifically 4-(azidosulfonyl)benzoic acid N-succinimidyl ester; 1.0 part of plasticizer, specifically oxazole-4-carboxamide; 0.5 parts of an oxidizing agent, specifically 4-vinylbenzylamine; Distilled water balance.
[0030] Example 3 According to 100 parts by weight of the following formula, the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the balance water are weighed in sequence and added into the reactor, and stirred and mixed at room temperature for 30 minutes to obtain the browning additive of this embodiment, which is then sealed and stored for later use.
[0031] 1.5 parts of the first corrosion inhibitor, whose structural formula is: ; The second corrosion inhibition is 1.5 parts, specifically alginate; 1.0 part of a cross-linking agent, specifically 3-maleimidopropionic acid N-hydroxysuccinimide ester; 1.0 part of plasticizer, specifically oxazole-5-carboxamide; 0.5 parts of an oxidizing agent, specifically N-benzylbutylamine; Distilled water balance.
[0032] Example 4 According to 100 parts by weight of the following formula, the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the balance water are weighed in sequence and added into the reactor, and stirred and mixed at room temperature for 30 minutes to obtain the browning additive of this embodiment, which is then sealed and stored for later use.
[0033] 3.0 parts of the first corrosion inhibitor, whose structural formula is: ; 3.0 parts of the second corrosion inhibitor, specifically guar gum; 2.0 parts of a cross-linking agent, specifically bis(bipyridine)-4'-methyl-4-carbonylpyridinium ruthenium-N-succinimidyl ester bis-hexafluorophosphate; 2.0 parts of plasticizer, specifically oxazole-2-carboxylic acid amide; 1.0 part of an oxidizing agent, specifically N-allylbenzylamine; Distilled water balance.
[0034] Example 5 According to 100 parts by weight of the following formula, the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the balance water are weighed in sequence and added into the reactor, and stirred and mixed at room temperature for 30 minutes to obtain the browning additive of this embodiment, which is then sealed and stored for later use.
[0035] 1.0 part of the first corrosion inhibitor, whose structural formula is: ; 1.0 part of the second corrosion inhibitor, specifically guar gum; 0.5 parts of a cross-linking agent, specifically bis(bipyridine)-4'-methyl-4-carbonylpyridinium ruthenium-N-succinimidyl ester bis-hexafluorophosphate; 0.5 parts of plasticizer, specifically oxazole-2-carboxamide; 0.2 parts of an oxidizing agent, specifically N-allylbenzylamine; Distilled water balance.
[0036] Example 6 According to 100 parts by weight of the following formula, the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the balance water are weighed in sequence and added into the reactor, and stirred and mixed at room temperature for 30 minutes to obtain the browning additive of this embodiment, which is then sealed and stored for later use.
[0037] 2.0 parts of the first corrosion inhibitor, whose structural formula is: ; 1.0 part of the second corrosion inhibitor, specifically guar gum; 0.5 parts of a cross-linking agent, specifically bis(bipyridine)-4'-methyl-4-carbonylpyridinium ruthenium-N-succinimidyl ester bis-hexafluorophosphate; 0.5 parts of plasticizer, specifically oxazole-2-carboxamide; 0.2 parts of an oxidizing agent, specifically N-allylbenzylamine; Distilled water balance.
[0038] Example 7 According to 100 parts by weight of the following formula, the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the balance water are weighed in sequence and added into the reactor, and stirred and mixed at room temperature for 30 minutes to obtain the browning additive of this embodiment, which is then sealed and stored for later use.
[0039] 1.0 part of the first corrosion inhibitor, whose structural formula is: ; 2.0 parts of the second corrosion inhibitor, specifically guar gum; 0.5 parts of a cross-linking agent, specifically bis(bipyridine)-4'-methyl-4-carbonylpyridinium ruthenium-N-succinimidyl ester bis-hexafluorophosphate; 0.5 parts of plasticizer, specifically oxazole-2-carboxamide; 0.2 parts of an oxidizing agent, specifically N-allylbenzylamine; Distilled water balance.
[0040] Example 8 According to 100 parts by weight of the following formula, the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, the oxidant and the balance water are weighed in sequence and added into the reactor, and stirred and mixed at room temperature for 30 minutes to obtain the browning additive of this embodiment, which is then sealed and stored for later use.
[0041] 1.5 parts of the first corrosion inhibitor, whose structural formula is: ; 1.5 parts of the second corrosion inhibitor, specifically guar gum; 1.0 part of a cross-linking agent, specifically bis(bipyridine)-4'-methyl-4-carbonylpyridinium ruthenium-N-succinimidyl ester bis-hexafluorophosphate; 1.0 part of plasticizer, specifically oxazole-2-carboxamide; 0.5 parts of an oxidizing agent, specifically N-allylbenzylamine; Distilled water balance.
[0042] In the process of exploring the browning effects of browning additives with different formulations, the present invention also prepared the following comparative examples of browning additives.
[0043] Comparative Example 1 The browning additive in Comparative Example 1 is different from that in Example 1 only in that the first corrosion inhibitor is not contained.
[0044] Comparative Example 2 The browning additive in Comparative Example 2 is different from that in Example 1 only in that it does not contain the second corrosion inhibitor.
[0045] Comparative Example 3 The browning additive in Comparative Example 3 is different from that in Example 1 only in that it does not contain a cross-linking agent.
[0046] Comparative Example 4 The browning additive in Comparative Example 4 is different from that in Example 1 only in that it does not contain a plasticizer.
[0047] Comparative Example 5 The browning additive in Comparative Example 5 is different from that in Example 1 only in that it does not contain an oxidant.
[0048] Comparative Example 6 The browning additive in Comparative Example 6 is different from that in Example 1 only in that the first corrosion inhibitor is 0.8 parts.
[0049] Comparative Example 7 The browning additive in Comparative Example 7 is different from that in Example 1 only in that the second corrosion inhibitor is 0.8 parts.
[0050] Comparative Example 8 The browning additive in Comparative Example 8 is different from that in Example 1 only in that the cross-linking agent is 0.2 parts.
[0051] Comparative Example 9 The browning additive in Comparative Example 9 is different from that in Example 1 only in that the amount of plasticizer is 0.2 parts.
[0052] Comparative Example 10 The browning additive in Comparative Example 10 is different from that in Example 1 only in that the oxidant is 0.1 part.
[0053] Comparative Example 11 The browning additive in Comparative Example 1 is different from that in Example 1 only in that the first corrosion inhibitor is 2.5 parts, the second corrosion inhibitor is 1.0 parts, and the mass ratio of the first corrosion inhibitor to the second corrosion inhibitor is 1:0.4 (lower than the range specified in the present invention).
[0054] Comparative Example 12 The browning additive of Comparative Example 12 is different from that of Example 1 only in that the first corrosion inhibitor is 1.0 parts, the second corrosion inhibitor is 2.5 parts, and the mass ratio of the first corrosion inhibitor to the second corrosion inhibitor is 1:2.5 (higher than the range specified in the present invention).
[0055] Comparative Example 13 The browning additive of Comparative Example 13 is a browning additive of the prior art (Chinese patent application CN110527996 A), and its specific components include: sulfuric acid, with a mass concentration of 200 g / L; hydrochloric acid, with a mass concentration of 50 mg / L; a mixture of benzotriazole and methyl imidazole-4-carboxylate (mass ratio of 5:2), with a mass concentration of 6 g / L; a mixture of citric acid and sodium citrate (mass ratio of 3:1), with a mass concentration of 15 g / L; nitric acid, with a mass concentration of 20 g / L; hydrogen peroxide, with a mass concentration of 20 g / L; and the solvent is distilled water.
[0056] The browning additives of the above-mentioned embodiments or comparative examples are used for browning of IC substrates (test samples), and the browning process flow is: S1 acid washing → S2 water washing → S3 degreasing → S4 water washing → S5 activation → S6 browning → S7 water washing → S8 drying. The details are as follows.
[0057] The S1 pickling process is to treat the IC substrate with an acidic solution to clean the surface impurities. The process parameters of the pickling process are: a spray method is used, the degreasing tank solution contains 2% sulfuric acid by mass, and the remainder is distilled water; the pickling tank is 2.0 m long, the tank temperature is 25±5 ℃, the line speed is 3.0±0.5 m / min, and the pressure is 1.5±0.5 kg / cm 2 ; The S2 washing process is to wash the IC substrate after the S1 pickling process. The process parameters of the washing process are: spraying method, washing tank length 2.0 m, tank temperature 25±5 ℃, line speed 3.0±0.5 m / min, pressure 1.5±0.5 kg / cm 2 ; The S3 degreasing process is to immerse the IC substrate after the S2 water washing process in an alkaline solution for degreasing. The process parameters of the degreasing process are: a spraying method is adopted, the degreasing tank solution contains 2% by mass of sodium hydroxide, and the balance is distilled water; the degreasing tank is 2.0 m long, the tank liquid temperature is 25±5 ℃, the line speed is 3.0±0.5 m / min, and the pressure is 1.5±0.5 kg / cm 2 ; The S4 washing process is to wash the IC substrate after the S3 degreasing process with DI water. The process parameters of the washing process are: spraying method, washing tank length 2.0 m, tank temperature 25±5 ℃, line speed 3.0±0.5 m / min, pressure 1.5±0.5 kg / cm2 ; The S5 activation process is to treat the IC substrate after the S4 washing process with an activation solution. The process parameters of the activation process are: a spraying method is adopted, the activation solution in the activation tank contains 3% by mass of the browning additive of the embodiment of the present invention or the comparative example, and the balance is distilled water (to prevent other liquids from being brought into the browning tank and causing pollution); the activation tank is 2.0 m long, the activation temperature is 25±5°C, the line speed is 3.0±0.5 m / min, and the pressure is 1.5±0.5 kg / cm 2 ; The S6 browning process is to treat the IC substrate after the S5 activation process with a browning solution. The process parameters of the browning process are: a spraying method is adopted, the browning solution in the browning tank contains 5% sulfuric acid, 2.5% hydrogen peroxide, 3% browning additives of the embodiment of the present invention or the comparative example, and the balance is distilled water; the browning tank is 2.0 m long, the tank liquid temperature is 25±5°C; the line speed is 3.0±0.5 m / min, and the pressure is 1.5±0.5 kg / cm 2 ; The S7 washing process is to wash the IC substrate after the S6 browning process with DI water to clean the surface impurities. The process parameters of the washing process are: spraying method, washing tank length 2.0 m, tank temperature 25±5 ℃, line speed 3.0±0.5 m / min, pressure 1.5±0.5 kg / cm 2 ; The S8 drying process is to dry the IC substrate after the S7 washing process, and the drying process parameters are: temperature 70±5°C, drying section length 2.0 m, and line speed 4.0±0.3 m / min.
[0058] The IC substrate (test sample) treated by the browning process in the above-mentioned embodiment or comparative example is subjected to the following performance tests, and the specific test method is as follows.
[0059] Roughness: Use a roughness measuring instrument to test the roughness value Ra of the copper surface after browning. The lower the Ra value, the more uniform the surface.
[0060] Peel strength: Take a 10cm*10cm substrate, etch off the copper foil on both sides, and then take a 10cm*10cm 1OZ copper foil and fix it on the substrate; press the IC carrier (test sample) treated by the browning process of the embodiment or comparative example with the 1OZ copper foil, cut out a 5cm*5cm test sample, and use a tensile testing machine to test its peel strength. The greater the peel strength, the better the bonding strength between the copper surface and the resin.
[0061] Insertion loss: The insertion loss (unit: db / inch) of the transmission line of each embodiment or comparative example IC substrate was tested at a test frequency of 25 GHz using a network analyzer. The lower the insertion loss, the better the integrity of the signal transmission.
[0062] Thermal stress test: First, the IC substrate (test sample) treated by the browning process is pretreated. The pretreatment condition is to bake the IC substrate in an oven at 125°C for 4 hours. After pretreatment, a tin immersion test is performed. The tin immersion test condition is to put the IC substrate into a 288°C tin solution for 10 seconds, and then place it in a ventilated place to cool naturally to room temperature. The tin immersion test is repeated 6 times to observe whether the IC substrate has delamination, fracture, or explosion. If not, the test result is qualified, otherwise it is unqualified.
[0063] Reflow test: First, pre-treat the IC substrate (test sample) after the browning process. The pre-treatment condition is to bake the IC substrate in an oven at 125°C for 4 hours. After pre-treatment, put the IC substrate into the reflow machine, and set the parameters to increase the temperature from 125°C by 20°C in each step to 265°C. Repeat the above steps 6 times to observe whether the IC substrate has delamination, fracture, or explosion. If not, the test result is qualified, otherwise it is unqualified.
[0064] The performance test results of the IC substrates of the above embodiments and comparative examples are shown in Table 1.
[0065] Table 1 Performance test results
[0066] It can be seen from the test results of Examples 1-8 in Table 1 that the surface roughness Ra value of the IC carrier obtained by using the browning additive of the present invention is stable at about 0.15. The low roughness indicates that the surface after browning is uniform, which is beneficial to reducing the insertion loss. The test shows that the insertion loss of the board surface is only about 0.61 db / inch, which has good signal integrity performance; at the same time, the peel strength of the board after browning is about 1.2 kg / cm, and the adhesion of the copper surface meets the production requirements; in the thermal stress test and reflow soldering test, the test sample has no delamination, fracture, or board explosion phenomenon, showing good heat resistance, and is suitable for application in the production of IC carrier browning process.
[0067] The difference between comparative examples 1-5 and embodiment 1 is that the browning additives lack a single component of the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer or the oxidant of the browning additive of the present invention, respectively. The test results show that the browning effect on the IC carrier is related to the effect of each additive component, and the lack of any component will affect the roughness, peel strength, insertion loss, thermal stress and reflow test effect of the browning. Among them, the first corrosion inhibitor and the second corrosion inhibitor have a synergistic effect. By utilizing the synergistic effect between the corrosion inhibitors with different polarities, when the ratio range of the two is appropriate, a multi-molecular layer anti-corrosion film with high coverage, good density and stability can be formed on the metal surface, effectively improving the adsorption rate. The crosslinking agent can have a strong adsorption force with the copper surface, can promote crosslinking and coupling, and is conducive to forming a multi-layer composite film on the surface of the copper foil, improving the quality of the organic metal film. The plasticizer is easy to form a coordination bond with the metal copper and is strongly adsorbed on the surface of the copper foil. It can also have a strong polymerization effect with the semi-cured resin, improve the bonding force between the metal and the resin, and can also form a layer of hydrophobic protective film on the metal surface to inhibit the erosion of the corrosive medium. The oxidant can form a moderately deep and uniform rough surface on the copper foil surface, providing favorable conditions for the formation of the organic metal film on the copper foil surface, and also helping to increase the contact area between the copper foil surface and the resin. When any of the first corrosion inhibitor, the second corrosion inhibitor, the crosslinking agent, the plasticizer, and the oxidant are missing from the components, the browning roughness, peel strength, insertion loss, thermal stress, and reflow test results are significantly reduced.
[0068] The difference between Comparative Examples 6-10 and Example 1 is that the first corrosion inhibitor, the second corrosion inhibitor, the cross-linking agent, the plasticizer, and the oxidant in the browning additives are respectively lower than the lower mass limit specified in the present invention. The test results show that the reduction in the content of each component will reduce the browning effect, and the roughness, peel strength, insertion loss, thermal stress and reflow test results are all significantly reduced, and the requirements for browning of IC substrates cannot be met. Therefore, the concentration of each component must be controlled within the scope of the present invention.
[0069] The difference between Comparative Examples 11 and 12 and Example 1 is that the mass ratio of the first corrosion inhibitor and the second corrosion inhibitor is higher and lower than the range specified in the present invention, respectively. The test results show that when the mass ratio of the first corrosion inhibitor and the second corrosion inhibitor exceeds the range specified in the present invention, the roughness, peel strength, insertion loss, thermal stress and reflow test results of the browning are significantly reduced. This indicates that the first corrosion inhibitor and the second corrosion inhibitor have a synergistic effect within the specified range. By utilizing the synergistic effect between corrosion inhibitors with different polarities, when the ratio of the two is appropriate, a multi-molecular layer anti-corrosion film with high coverage, good density and stability can be formed on the metal surface, effectively improving the adsorption rate. Therefore, the mass ratio of the first corrosion inhibitor and the second corrosion inhibitor must be controlled within the scope of the present invention.
[0070] Comparative Example 13 uses the chemical browning liquid of the prior art, and the test results thereof are compared with the test results of Examples 1-5, indicating that the browning additive of the present invention has lower roughness, higher peel strength, and lower insertion loss.
[0071] Example 1: SEM image of IC substrate after browning process Figure 2 As shown; Comparative Example 13 The SEM image of the IC substrate after the browning process is as shown Figure 3 shown.
[0072] In summary, the browning additive of the present invention is suitable for the browning process of IC substrates. The browning additive contains a first corrosion inhibitor, a second corrosion inhibitor, a cross-linking agent, a plasticizer, and an oxidant. It can form a layer of organic metal film on the uneven active microscopic rough copper surface, which can effectively improve the uniformity and bonding strength of the copper surface after browning, so that it has low roughness, high peel strength, low insertion loss and good heat resistance, meeting the production requirements of the IC substrate browning process.
[0073] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A browning additive, characterized in that: The composition is composed of the following ingredients per 100 parts by weight: 1.0-3.0 parts of the first corrosion inhibitor, 1.0-3.0 parts of the second corrosion inhibitor, 0.5-2.0 parts of the crosslinking agent, 0.5-2.0 parts of the plasticizer, 0.2-1.0 parts of the oxidant, and the balance is water; The structural formula of the first corrosion inhibitor is as follows: ; wherein R is F, Cl, Br or I; The second corrosion inhibitor is selected from at least one of guar gum, locust bean gum and alginate; The mass ratio of the first corrosion inhibitor to the second corrosion inhibitor is 1:(0.5-2.0).
2. The browning additive according to claim 1, characterized in that The crosslinking agent is selected from at least one of bis(bipyridine)-4'-methyl-4-carbonylpyridinium ruthenium-N-succinimide ester bishexafluorophosphate, 4-(azidosulfonyl)benzoic acid N-succinimide ester, and 3-maleimidopropionic acid N-hydroxysuccinimide ester.
3. The browning additive according to claim 1, characterized in that The plasticizer is selected from at least one of oxazole-2-carboxylic acid amide, oxazole-4-carboxylic acid amide and oxazole-5-carboxylic acid amide.
4. The browning additive according to claim 1, characterized in that The oxidant is selected from at least one of N-allylbenzylamine, 4-vinylbenzylamine and N-benzylbutylamine.
5. The browning additive according to claim 1, characterized in that The first corrosion inhibitor is prepared by mixing 1,2-diphenylethanedione, p-aminoanisole, p-halobenzaldehyde and acetic acid in water, reacting at 60-70° C. for 4-6 hours, and after the reaction, adjusting the pH of the resulting solution to 7-8, and then extracting with ethyl acetate to obtain the first corrosion inhibitor.
6. The browning additive according to claim 5, characterized in that The mass ratio of the 1,2-diphenylethanedione, p-aminoanisole, p-halobenzaldehyde and acetic acid is (2-3): (2-3): (2-3):
1.
7. A method for browning an IC substrate, characterized in that: The following steps are included in sequence: Activation: Activating the IC substrate with an activation solution; the activation solution is an aqueous solution of the browning additive according to any one of claims 1 to 6 with a mass concentration of 3-4%; Browning: The IC substrate is browned using a browning solution; the browning solution is composed of the following components in mass fractions: 3-5% of the browning additive as described in any one of claims 1 to 6, 4-6% of sulfuric acid, 2-3% of hydrogen peroxide, and the balance is water.
8. The method for browning an IC substrate according to claim 7, characterized in that: The activation solution is used to activate the IC substrate, specifically: the activation solution is sprayed on the IC substrate at a spray pressure of 1.5±0.5kg / cm 2 , time 35-50S.
9. The method for browning an IC substrate according to claim 7, characterized in that: The browning treatment of the IC substrate with the browning solution is specifically as follows: the IC substrate is sprayed with the browning solution at a spraying pressure of 1.5±0.5kg / cm 2 , time 35-50S.
10. The method for browning an IC substrate according to claim 7, characterized in that: Before the activation step, it also includes pickling, degreasing and water washing.
Citation Information
Patent Citations
Browning liquid as well as preparation method and application thereof
CN110527996A
Brownification fluid for processing printed circuit board on basis of functionalized ionic liquid
CN104928667A
Browning treatment liquid for printed circuit board
CN105714280A
Circuit board inner layer copper foil brown liquid
CN111826645A
Etching composition for copper and molibdenum containing film
KR1020150039526A